Scientific literacy-based encyclopedia on the antiaging properties of acehnese spices: A research and development approach - Fiyantara, Aljun; Diningrat, Diky Setya; Hasairin, Ashar; Hartono, Adi; Salleh, Rabeta Mohd; Sari, Ayu Nirmala (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2025)
The aim of this research is to produce an encyclopedia of Acehnese spice plants that serves as an anti-aging agent developed based on scientific literacy. The encyclopedia of Acehnese spice plants will be used as one of the learning media in the Ethnobotany course. The development procedure was carried out using the ADDIE method which includes analyzing student needs and characteristics, formulating learning objectives, formulating material items, preparing evaluation instruments, writing drafts of encyclopedia, expert validation, field trials, and printing production scripts. Ethnobotanical experts conducted expert validation. The results of the expert validation test stated that the encyclopedia of Acehnese spice plants with antiaging potential as a learning resource to improve student science literacy in ethnobotany courses followed the design and the material included in it was suitable for use as learning media. The field trial results showed that the science literacy-based encyclopedia was very attractive in design and effectively used as learning media.